Are private banks more sensitive to changes in reserve requirements? Evidence from an emerging market - Swamy, Vighneswara (2025)
Purpose: This article explores the effects of monetary policy rates and interest rate structures on bank profitability. Design/methodology/approach: We studied 65 Indian commercial banks over time, including economic cycles, consolidation and the Great Financial Crisis. We categorized commercial banks by ownership (public, private or foreign) and predicted how they will react to monetary policy changes. We employed the instrumental variable estimate approach and panel Granger causality tests to give evidence of the direction of causation in the monetary policy and bank performance nexus. Findings: Private and international banks, we believe, are more sensitive to changes in reserve requirements because they are more effective at maintaining statutory reserves. Private and international banks are more susceptible to repo rate fluctuations than state banks. In contrast, public banks are more sensitive to bank rates because they are more likely than private and international banks to use the bank rate window of accommodation. Originality/value: We studied the impact of monetary policy rates on bank performance within the banking-dominated financial system of an emerging economy – a focus that has not been previously explored. There has been little research into the connection between monetary policy rates and bank performance in emerging markets, notably in India.